VIR COLLECTION - FOR THE SELECTION OF SERVICE - V. I. Burenin; T. M. Piskunova (Овощи России, 2012)
The article marked the stages of formation and studying of the VIR's collection of vegetable and melon crops. The structure of the collection and its significance for breeding is shown. The most important genetic resources of economically important traits are given.